Laser biosensor use for the microbial metabolic activity assessment of kefir vinegar - Magalhães-Guedes, Karina Teixeira; Viana, Roberta Oliveira; Braga Junior, Roberto Alves; Dias, Disney Ribeiro; Ferreira, Camila Duarte; Nunes, Itaciara Larroza; Schwan, Rosane Freitas (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to verify the use of a laser biosensor for the microbial metabolic activity assessment of kefir vinegar. Kefir grains were inoculated in apple must and were analyzed daily using the biospeckle technique. The initial biological activity was of 14.21 pixels per absolute value of differences (AVD). The biological activity of kefir grains decreased in the early days of fermentation and increased on the fourth day to 11.51 pixels per AVD; however, on the last day, the biological activity of kefir grains decreased to 7.12 pixels (alcoholic fermentation) and to 6.77 pixels per AVD (acetic fermentation). This new biospeckle methodology facilitates the microbiological control in fermentation processes.